A case of juvenile polyposis of the stomach with multiple early gastric cancers - SAITO, RYUSUKE (Mol Clin Oncol, 2016)
The present study described the case of a 24-year-old man who was diagnosed with multiple gastric hyperplastic polyps in 2004. Repeated Helicobacter pylori tests were negative, and colonoscopy revealed no specific findings. The patient started taking a proton-pump inhibitor and iron supplements as a result of anemia caused from the occasional bleeding from the polyps. The number and size of the polyps had increased over time. Endoscopic mucosal resection was occasionally performed when bleeding occurred from large polyps. Finally, histological examination revealed that the surface of the polyp had been replaced with well-differentiated adenocarcinoma in 2014. Laparoscopy-assisted total gastrectomy with Roux-en-Y esophagojejunostomy was performed in 2014. The final diagnosis was juvenile polyposis of the stomach with multiple early gastric cancers. Juvenile polyposis of the stomach is a rare disease, and its malignant potential has been reported previously. The present case highlighted the importance of not delaying surgical intervention in cases of juvenile polyposis of the stomach, since it is associated with a high occurrence of gastric cancer.